Map scheme of the housing fund of the Zhytomyr region: qualitative and quantitative analysis - Karas, I.; Kotkova, T.; Pitsil, A.; Voitenko, S.; Lukhianenko, O. (Land Management, Cadastre and Land Monitoring, 2022)
The housing fund, as a concept, is a complex of interrelated indicators characterizing its condition. First of all, it is the availability of housing, that is, the amount of living space per person of the population. This also includes the total living area, the number of houses and apartments, and the equipment of the housing stock by types of terrain.It is known that Ukraine has almost the lowest rate of housing security among European countries. It is about 29 m2/person. While other countries have much higher housing affordability, ranging from 31,2m2/person (Estonia) to 66,3m2/person (Luxembourg). The reasons for this state of affairs in our country are the inefficient use of land within categories, the inaccessibility of housing for many segments of the population, the lack of state programs for financing construction and lending housing, low wages, etc.The goal of our research was to study the housing stock of the Zhytomyr region with further analysis of its condition.Based on the results of the research, maps of the provision of housing for the urban and rural population in the sections of Zhytomyr regiont were constructed. The largest amount of living space per person was observed in Brusylivskiy, Ruzhynskiy, Popilnyanskiy and Narodytskiy districts (30–40 m2). Moreover, security in rural areas is somewhat higher than in urban areas. In our opinion, the reason for this is the lower population concentration in small settlements. Therefore, population size as a factor influencing the condition of the housing stock of Zhytomyr region is one of the main, but not the only factors.It was also established that over the past 15 years, the average housing supply in the region increased from 23,3 m2 to 28,3 m2 per person, while the number of apartments and houses actually remained at the same level (968,1 thousand in 2005 and 974,4 thousand in 2020), and the population has decreased significantly. Therefore, the reason for the increase in the housing supply indicator is not the improvement of the quantitative and qualitative condition of the housing stock of the Zhytomyr region, but rather the decrease in the number of residents.Along with the quantitative analysis, a qualitative analysis of the housing stock was also conducted. It has been established that housing equipment with plumbing, sewage, and hot water has increased by almost 50% over the past fifteen years, especially in rural areas. And in general, the qualitative characteristics of the housing stock in the Zhytomyr region are somewhat inferior to similar ones in Ukraine.
Keywords: housing stock; Zhytomyr region; housing supply; rural area; urban area; housing stock equipment